CLARIFYING THE NATURE OF THE HECKMAN CURVE. (3rd February 2020) - Rea, David; Burton, Tony
Abstract: In response to our paper, we understand that James Heckman communicated to the journal Editors states that the Heckman Curve does not describe how the average return on investment of programs differs by the age of recipients. This clarification is useful as many people in the policy community have understood the Heckman Curve in this manner.